2003
DOI: 10.1042/bst0310731
|View full text |Cite
|
Sign up to set email alerts
|

Human porphobilinogen deaminase mutations in the investigation of the mechanism of dipyrromethane cofactor assembly and tetrapyrrole formation

Abstract: Porphobilinogen deaminase mutants that cause acute intermittent porphyria have been investigated as recombinant proteins expressed in Escherichia coli, yielding important insight into the mechanism of dipyrromethane cofactor assembly and tetrapyrrole chain polymerization. A mutation that affects a key catalytic residue, D99G, results in an inactive holo -protein that exists as a complex with two substrate molecules covalently bound to the dipyrromethane cofactor arising from the reaction between the apo -prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
3
13
0
1
Order By: Relevance
“…The missing coordinates of the residues 60-78 (part of the active-site loop and adjoining region) were modeled based on the structure of AtHMBS [PDB ID code 4HTG (10)] using Modeler 9v8 (22). The missing residues at the N-terminal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the C-terminal (residues 358-361) were also modeled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The missing coordinates of the residues 60-78 (part of the active-site loop and adjoining region) were modeled based on the structure of AtHMBS [PDB ID code 4HTG (10)] using Modeler 9v8 (22). The missing residues at the N-terminal (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and the C-terminal (residues 358-361) were also modeled.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the purified Escherichia coli and human enzymes demonstrated the critical importance of a covalently bound dipyrromethane (DPM) cofactor and the occurrence of stable enzyme substrate complexes in the formation of HMB (4,(6)(7)(8). To date, the X-ray crystal structures of E. coli (9), Arabidopsis thaliana (10), Bacillus megaterium (11,12), and human (13,14) HMBS (hHMBS) with their DPM cofactors have been reported.…”
mentioning
confidence: 99%
“…Arg173 is an invariant residue in all known sequences. The mutation of Arg173 to Gln results in an apo form of the enzyme that is incapable of catalysis [26]. The missense mutant p.Arg173Trp in AIP patients has also been found to be inactive [27].…”
Section: Resultsmentioning
confidence: 99%
“…The bulky arginine moiety in the mutant may disrupt the docking or covalent binding of the cofactor to the enzyme, while a charge switch in the p.Lys98Glu mutant has no such effect. Several other mutants (Arg149Gln, Arg173Gln38 and Arg116Trp)39 are also reported to result in the expression of apoenzyme. It is suggested that the disrupted interaction of these residues with the cofactor likely prevents successful docking of hydroxymethylbilane, the DPM precursor, in the active site of the apoenzyme.…”
Section: Discussionmentioning
confidence: 99%